2019
DOI: 10.1104/pp.18.01133
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Integrity of Lignin Is Crucial for Resistance against Striga hermonthica Parasitism in Rice

Abstract: Striga species are parasitic weeds that seriously constrain the productivity of food staples, including cereals and legumes, in Sub-Saharan Africa and Asia. In eastern and central Africa, Striga spp. infest as much as 40 million hectares of smallholder farmland causing total crop failure during severe infestation. As the molecular mechanisms underlying resistance are yet to be elucidated, we undertook a comparative metabolome study using the Striga-resistant rice (Oryza sativa) cultivar 'Nipponbare' and the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 63 publications
3
49
0
Order By: Relevance
“…O-Methyltransferase (PMT) [27] and NAC domain transcription factor [28]. Both of these genes are involved in lignin biosynthesis and regulation, consistent with numerous studies that describe lignin as an important component in Striga resistance [29,30]. In addition to cell wall forti cation, hosts may protect themselves against parasitic cell wall degrading enzymes such as a pectinesterases using their cognate inhibitors [21,31].…”
Section: Genetic Causes Of Striga Resistancesupporting
confidence: 68%
“…O-Methyltransferase (PMT) [27] and NAC domain transcription factor [28]. Both of these genes are involved in lignin biosynthesis and regulation, consistent with numerous studies that describe lignin as an important component in Striga resistance [29,30]. In addition to cell wall forti cation, hosts may protect themselves against parasitic cell wall degrading enzymes such as a pectinesterases using their cognate inhibitors [21,31].…”
Section: Genetic Causes Of Striga Resistancesupporting
confidence: 68%
“…A study by Mutuku et al (2019) demonstrated that, upon infection of Striga hermonthica in rice, the accumulation of metabolites related to the deposition of lignin was observed at the site of infection. Lignin makes up the cell wall of vascular plants and is induced upon biotic stress [50]. A rapid burst of ROS was observed as one of the earliest events after the imposition of stress [51].…”
Section: Mqtl25mentioning
confidence: 99%
“…Many phenolic HIFs are lignin precursors and, therefore, can be incorporated into lignin polymers in the secondary cell walls of hosts or parasitic plants. Lignin is known to be involved in physical defense against various pathogens including bacteria, fungi, plant-parasitic nematodes, and parasitic plants (Goldwasser et al, 1999; Bhuiyan et al, 2009; Miedes et al, 2014; Khanam et al, 2018; Mutuku et al, 2019). Lignin is deposited at the Striga infection site in a Striga -resistant rice cultivar, and lignin modification in the rice host affects resistance against Striga (Mutuku et al, 2019).…”
Section: Roles Of Hifs In Host-parasitic Plant Interactions After Prementioning
confidence: 99%